2014
DOI: 10.3109/00365521.2014.886715
|View full text |Cite
|
Sign up to set email alerts
|

European panel on the appropriateness of gastrointestinal endoscopy II guidelines help in selecting and prioritizing patients referred to colonoscopy – a quality control study

Abstract: The majority of colonoscopies were found appropriate by EPAGE II. There was a clear association between high appropriateness of the indication and a high DY. EPAGE II is a guideline-improvement that may be useful for both referring physicians and gastroenterologists when considering referrals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 106 publications
0
14
0
1
Order By: Relevance
“…In primary care practices in Switzerland, 14% of colonoscopy referrals and 49% of referrals for upper endoscopy represented overuse. 114,115 Elsewhere in Europe, appropriateness rates for endoscopy have been reported in Portugal, Spain, Italy, and Norway, with overuse accounting for between 13% and 33% of tests, 116119 and at an Israeli center 16% of endoscopies were unnecessary. 120 Studies in the US have reported overuse rates as high as 60% 121 .…”
Section: Worldwide Prevalence Of Overusementioning
confidence: 99%
“…In primary care practices in Switzerland, 14% of colonoscopy referrals and 49% of referrals for upper endoscopy represented overuse. 114,115 Elsewhere in Europe, appropriateness rates for endoscopy have been reported in Portugal, Spain, Italy, and Norway, with overuse accounting for between 13% and 33% of tests, 116119 and at an Israeli center 16% of endoscopies were unnecessary. 120 Studies in the US have reported overuse rates as high as 60% 121 .…”
Section: Worldwide Prevalence Of Overusementioning
confidence: 99%
“…Assessing colonoscopy indications prospectively, and concluding whether or not colonoscopy results modified patient management, would provide further elements to determine whether colonoscopy requests were appropriate. However, studies that assess appropriateness of colonoscopy prospectively, obtain similar results [ 26 , 30 , 32 ].…”
Section: Discussionmentioning
confidence: 90%
“…As one example, a meta‐analysis has shown that the diagnostic OR of the American Society for Gastrointestinal Endoscopy and European Panel on the Appropriateness of Gastrointestinal Endoscopy (EPAGE) criteria for relevant findings was 2.5 (95% CI: 1.2–5.6), inferior to the OR of the FAST Score in both derivation and the validation cohorts. Further, although we cannot exclude relevant findings in the low risk group (PPV: 5.2–5.3%), the PPV in the inappropriate colonoscopy group according to the EPAGE II criteria ranges between 9.5 and 24.5% . Finally, it is quite clear that the main endpoint of endoscopic evaluation of symptomatic patients must be the detection, or perhaps more importantly, the exclusion of those clinical conditions that threaten or significantly affect the quality of life, especially on account of the limited endoscopic resources available in many countries.…”
Section: Discussionmentioning
confidence: 93%